Increase of durability of three-cone rock bit cutters - D. Yu.Petryna, R. S.Yakym (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2018)
The influence of physico-mechanical and technological indices on the crack resistance of different melting of 14HN3MA-B steel for three-cone rock bit cutters has been studied. When the strength index values of rock bit steel melting are about DI=4.0 or in the case of the tendency of this steel to crack formation, the rolled stock shall be subjected to diffusion annealing prior to forging. The cone blank manufacturing shall be performed by forging of rolled stock if the deformation is not less than ε=40 %. It is also necessary to perform the quench to 830±10 °С after carbonizing, and the second hardening shall be performed with temperature of 870 ºС as a starting point.